Pendampingan Edukasi Kopi Robusta Bagi Siswa PKL SMK – PP Ambon di CV. Kopi Citarasa Persada - Ika Sari Tondang; Nabella Ayu Wulandari (Harmoni Sosial : Jurnal Pengabdian dan Solidaritas Masyarakat, 2024)
CV.Kopi Citarasa Persada operates in the field of educational agrotourism and explains the processing of coffee and its derivatives. Support is provided to support this educational agrotourism activity. The aim of this support effort is to make the company an educational tourism destination for coffee production and utilize the potential of coffee raw materials in Tutur District to provide knowledge about coffee to various groups ranging from children to adults. An aspect that differentiates CV. Kopi Citarasa Persada is a comprehensive approach to coffee processing from upstream to downstream. They have developed educational tours that allow visitors to experience firsthand the process of growing Robusta coffee. There are several interesting locations in this educational tour. Educational tourism support activities at CV. Kopi Citarasa Persada offers a variety of experiences in interesting places with a variety of knowledge gains. This educational tourism support has had a positive impact, especially for pkl students. You will expand your knowledge about the history of Robusta coffee cultivation and understand the processing process of ground coffee and its various derivative products in more detail.